Oncology teaching in undergraduate medical school - Proposed discipline - Wainstein, Alberto J.A.; Azevedo, Sergio J; Marta, Gustavo N; Canary, Paulo C; Rodrigues, Angelica Nogueira; Sternberg, Cinthya; Santos, Fernando A V; Drummond-Lage, Ana Paula (Brazilian Journal of Oncology, 2020)
Cancer is the main public health problem in Brazil and the world, and if the National Oncological Care Policy is not modified, cancer will become the leading cause of death in the country in 2029. However, the guidelines of the Ministry of Education do not have oncology as a necessary or mandatory discipline in medical schools. It means despite all the importance of cancer globally and, not unlike in Brazilian society, there is no obligation for the discipline of oncology in Brazilian medical graduation, which incurs in the incomplete training of academics, not allowing them to develop concepts and skills with a vision integrated cancer. In this article, a group of specialists in oncology in the primary, clinical, surgical, radiotherapy, and cancer research areas, proposes a Cancerology discipline syllabus for undergraduate medical students in Brazil. We sought to present the objectives of the discipline, the subjects to be addressed, the format of the classes, and the workload in a systematic way.
Keywords: Education, Graduate; Education, Medical; Medical Oncology; Radiation Oncology; Integrative Oncology; Basic Research